Diabetes and gender incongruence: frequent mental health issues but comparable metabolic control – a DPV registry study - Boettcher, Claudia; Tittel, Sascha R.; Reschke, Felix; Fritsch, Maria; Schreiner, Felix; Achenbach, Maike; Thiele-Schmitz, Susanne; Gillessen, Anton; Galler, Angela; Nellen-Hellmuth, Nicole; Golembowski, Sven; Holl, Reinhard W. (Frontiers in Endocrinology, 2024)
Context The condition when a person’s gender identity does not match the sex assigned at birth is called gender incongruence (GI). Numbers of GI people seeking medical care increased tremendously over the last decade. Diabetes mellitus is a severe and lifelong disease. GI combined with diabetes may potentiate into a burdensome package for affected people. Objective The study aimed to characterize people with GI and diabetes from an extensive standardized registry, the Prospective Diabetes Follow-up Registry (DPV), and to identify potential metabolic and psychological burdens. Methods We compared demographic and clinical registry data of persons with type 1 or type 2 diabetes and GI to those without GI and used propensity score matching (1:4) with age, diabetes duration and treatment year as covariates. Results 75 persons with GI, 49 with type 1 and 26 with type 2 diabetes were identified. HbA1c values were similar in matched persons with type 1 or 2 diabetes and GI compared to those without GI. Lipid profiles showed no difference, neither in type 1 nor in type 2 diabetes. Diastolic blood pressure was higher in the type 1 and GI group than in those without, whereas systolic blood pressure showed comparable results in all groups. Depression and anxiety were significantly higher in GI people (type 1 and 2). Non-suicidal self-injurious behaviour was more common in type 1 and GI, as was suicidality in type 2 with GI. Conclusion Mental health issues are frequent in people with diabetes and GI and need to be specially addressed in this population.